Investigation of Analgesic and Anti Inflammatory Potential of Ethanolic Extract of Atylosia rugosa - Mare, Prathibha Bharathi (International Journal of Pharmaceutical & Biological Archive, 2015)
Investigation of Analgesic and Anti Inflammatory Potential of Ethanolic Extract of Atylosia rugosa